Dendritic Cells in the Cross Hair for the Generation of Tailored Vaccines - Gornati, Laura; Zanoni, Ivan; Granucci, Francesca (Frontiers in Immunology, 2018)
Vaccines represent the discovery of utmost importance for global health, due to both prophylactic action to prevent infections and therapeutic intervention in neoplastic diseases. Despite this, current vaccination strategies need to be refined to successfully generate robust protective antigen-specific memory immune responses. To address this issue, one possibility is to exploit the high efficiency of dendritic cells (DCs) as antigen presenting cells for T cell priming. DCs functional plasticity allows shaping the outcome of immune responses to achieve the required type of immunity. Therefore, the choice of adjuvants to guide and sustain DCs maturation, the design of multifaceted vehicles and the choice of surface molecules to specifically target DCs, represent the key issues currently explored in both preclinical and clinical settings. Here, we review advances in DCs-based vaccination approaches, which exploit direct in vivo DCs targeting and activation options. We also discuss the recent findings for efficient anti-tumor DCs-based vaccinations and combination strategies to reduce the immune tolerance promoted by the tumor microenvironment.